REGENERATION AS AN EMERGING PARADIGM: OVERCOMING SUSTAINABILITY IN CONTEMPORARY SOCIOENVIRONMENTAL THOUGHT - de Giorge Cerqueira, Homero (Revista Gênero e Interdisciplinaridade, 2025)
This research investigates the emergence of the regenerative paradigm as a conceptual and practical overcoming of the sustainability model in contemporary socio- environmental thinking. Through a theoretical-conceptual analysis based on systematic literature review, this study examines the epistemological, philosophical and practical foundations that support the transition from sustainability to regeneration. The general objective is to critically analyze the limitations of the sustainability paradigm and demonstrate how the regenerative paradigm offers a more robust alternative to face the socio-environmental crisis of the Anthropocene. The methodology employed combines documentary analysis, specialized literature review and practical case studies. The results indicate that the regenerative paradigm, grounded in deep ecology, systems thinking and principles of regenerative economics, represents a paradigmatic shift that transcends the mitigating logic of sustainability, proposing a restorative and co- evolutionary approach. The conclusions point to the need for a systemic transformation that integrates ecological, social, economic and spiritual dimensions, configuring a new social and environmental contract based on active regeneration of living systems.